An auxiliary study of the smart grid deployment in India. Philosophy and key drivers. (2016) - Beg, Farhan
With an ever increasing population coupled with a perpetual depletion of fossil fuel resources and many generation sites attaining their ultimate capacity, India is in dire need of an up gradation of its electrical infrastructure. A much smarter approach towards the electrical grid is needed. This smarter approach technically referred to as the 'smart grid', promises an affordable electrical environment. This paper presents the journey of the Indian power sector through time, analyses various demand and supply scenarios which are mutually exclusive and also assesses various issues facing the Indian power system. This paper also highlights the need for ICT infrastructure concepts as well as various technologies involved to deploy a smart grid infrastructure and thereby leading to a conception of safety by means of design and modification resulting in an enhanced electricity management environment and hence leading to energy independence and an electrical grid that is much more reliable, secure, efficient, and greener.